2023
DOI: 10.1111/jcmm.17758
|View full text |Cite
|
Sign up to set email alerts
|

Engeletin alleviates cerebral ischemia reperfusion‐induced neuroinflammation via the HMGB1/TLR4/NF‐κB network

Abstract: High-mobility group box1 (HMGB1) induces inflammatory injury, and emerging reports suggest that it is critical for brain ischemia reperfusion. Engeletin, a natural Smilax glabra rhizomilax derivative, is reported to possess anti-inflammatory activity.Herein, we examined the mechanism of engeletin-mediated neuroprotection in rats having transient middle cerebral artery occlusion (tMCAO) against cerebral ischemia reperfusion injury. Male SD rats were induced using a 1.5 h tMCAO, following by reperfusion for 22.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…It has been determined that HMGB1/TLR4/NF-κB inflammatory network and its downstream mediators (IL-1β and TNF-α) as well as NLRP3 inflammasomemediated neuroinflammatory responses in the brain (Su et al, 2022;Xu et al, 2023). Investigation on ASD patients reveals a higher level of pro-inflammatory cytokines, including IL-1β and TNF-α (Chan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It has been determined that HMGB1/TLR4/NF-κB inflammatory network and its downstream mediators (IL-1β and TNF-α) as well as NLRP3 inflammasomemediated neuroinflammatory responses in the brain (Su et al, 2022;Xu et al, 2023). Investigation on ASD patients reveals a higher level of pro-inflammatory cytokines, including IL-1β and TNF-α (Chan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…For example, nuclear factor-kappa B (NF-κB) and the subsequent transcription of various pro-inflammatory genes were activated afterward. This results in the production and secretion of pro-inflammatory cytokines including TNF-α, IL-1β, and IL-6 ( Xie et al, 2019 ; Xu et al, 2023 ). HMGB1 can also promote the expression and activity of MMPs, especially MMP-9, thus altering the function of TJPs and consequently increasing BBB permeability ( Richard et al, 2017 ).…”
Section: Inflammatory Markersmentioning
confidence: 99%
“… 15 , 16 In addition, it has been shown to exert neuroprotective activity, suppressing the production of reactive oxygen species and mitigating the severity of ischemia/reperfusion injury and Alzheimer's disease. 17 , 18 Preliminary research conducted by our group further revealed that engeletin can alleviate depressive‐like behaviours induced by chronic restraint stress through its ability to modulate the brain‐derived neurotrophic factor (BDNF)/TrkB/mTORC1 signalling axis, thereby enhancing synaptic plasticity. 19 However, no research to date has evaluated the effects of engeletin on the regulation of the M1/M2 polarization of microglia.…”
Section: Introductionmentioning
confidence: 99%